Inflammation and Invasion in Oral Squamous Cell Carcinoma Cells Exposed to Electronic Cigarette Vapor Extract - Robin, Hannah P.; Trudeau, Courtney N.; Robbins, Adam J.; Chung, Emily J.; Rahman, Erum; Strickland, Olivia L. Gangmark; Jordan, Scott; Licari, Frank W.; Winden, Duane R.; Reynolds, Paul R.; Arroyo, Juan A. (Frontiers in Oncology, 2022)
Electronic cigarettes (eCig) represent a new avenue of tobacco exposure that involves heating oil-based liquids and the delivery of aerosolized flavors with or without nicotine, yet little is known about their overall health impact. The oral cavity is an anatomic gateway for exposure that can be compromised by activating myriad of signaling networks. Oral squamous cell carcinoma (OSSC) is a common malignancy affecting 30,000 people in the United States each year. Our objective was to determine the impact of eCig and nicotine on gingival OSSC invasion and their secretion of pro-inflammatory molecules. Gingiva-derived Ca9-22 cells and tongue-derived Cal27 cells were exposed to eCig vapor extract (EVE) generated from Red Hot or Green Apple (Apple) flavored eCig solution +/- nicotine for 6 hours. Isolation of protein lysates and collection conditioned media was done after treatment. Real-time cellular invasion was assessed using a RTCA DP instrument. Protein expression was determined using western blot. Compared to controls, we observed: elevated NF-kB, TNF-α, ERK, JNK, MMP-13 and cell invasion by Ca9-22 treated with Apple EVE; increased TNF-α and JNK by Ca9-22 treated with Red Hot EVE; and increased TNF-α and JNK by Cal27 cells treated with both Apple and Red Hot EVE. We conclude that eCig flavoring and nicotine orchestrated differential cell invasion and inflammatory effects. This study provides an important initial step in dissecting mechanisms of cancerous invasion and molecular avenues employed by OSCC.